2016
DOI: 10.1080/17597269.2016.1192445
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of coconut oil ethyl esters reaction variables and prediction model of its blends with diesel fuel for density and kinematic viscosity

Abstract: This paper presents the synthesis of biodiesel from coconut oil sourced from Nigeria through base-catalyzed transesterification using potassium hydroxide (KOH) as catalyst and ethanol as solvent. Direct transesterification reactions were carried out due to low free fatty acid value (0.65 mg KOH/g oil). The reaction variables optimized were: KOH amount (0.5À2.25 wt.%), reaction temperature (30À80 C), reaction time (30À70 min) and ethanol to oil molar ratio (3À12). Physico-chemical properties of the coconut oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 46 publications
0
10
0
Order By: Relevance
“…Moreover, the separation of the BD from glycerin during settlement becomes very hard. [47][48][49] It was observed that increasing the reaction temperature enhanced the BD yield as a fact that the separation of glycerin may be accelerated by raising the reaction temperature. 41 Similar findings were also announced by Eevera and Pazhanichamy 42 and Verma et al 43 Alcohol is a basic reactant during the alcoholysis reaction because it owns a great impact on the conversion.…”
Section: Alcoholysis Of Mixed Ro and Ako With Different Alcoholsmentioning
confidence: 99%
“…Moreover, the separation of the BD from glycerin during settlement becomes very hard. [47][48][49] It was observed that increasing the reaction temperature enhanced the BD yield as a fact that the separation of glycerin may be accelerated by raising the reaction temperature. 41 Similar findings were also announced by Eevera and Pazhanichamy 42 and Verma et al 43 Alcohol is a basic reactant during the alcoholysis reaction because it owns a great impact on the conversion.…”
Section: Alcoholysis Of Mixed Ro and Ako With Different Alcoholsmentioning
confidence: 99%
“…Oil having viscosity might cause engine misfiring, engine deposits and poor atomization in diesel engines [44][45]. The flash point (FhP) of the PKO (242 0 C) was within the range of the earlier works reported by other researchers [38,40,41]. However, the FhP was much higher than the specified value of European and American standards.…”
Section: Resultsmentioning
confidence: 59%
“…These properties, namely, viscosity, density, flash point and pour points, are further compared with those of coconut oil (CNO), waste cooking oil (WCO), palm kernel oil and Jatropha seed oil from other researchers. The density of PKO (895 kg/m3) was lower than the density of oils specified by other researchers [38][39][40][41][42][43] and it was within the range specified by European Union standard (860 -900 kg/m 3 ). The viscosity of PKO (33.20 mm 2 /s) was comparable to those of other researchers [38,39,41,43] and it was within the norms specified by European Union specification (3.5 -5.0 mm 2 /s) and ASTM standard (1.9 -6.0 mm 2 /s).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations